KEPEMILIKAN RUMAH SUSUN OLEH WARGA NEGARA ASING DALAM MEWUJUDKAN KEPASTIAN HUKUM - Udjan, Bernadeth Gisela Lema; Sari, Retno Dewi Pulung (Legal Standing : Jurnal Ilmu Hukum, 2024)
This research aimed to critically analyze regulations regarding the ownership status of flats in realizing legal certainty. The research method used is normative juridical research using a library study model. This research uses a legislative regulation strategy. The research results show that the concept of apartment ownership, which has been regulated in statutory regulations, has different rules. The UUPA firmly states that only Indonesian citizens (WNI) have rights to land with the status of Ownership Rights, Business Use Rights, and Building Use Rights. In contrast, the Job Creation Law states that foreigners are allowed to have ownership of Building Use Rights (HGB) without changing the right becomes the Right to Use. However, Building Use Rights (HGB) can only be owned by Indonesian citizens, and ownership can be given to foreigners who have a residence permit with the requirement of completing the house shape criteria that the government itself has regulated.